GENDER EQUITY AND INCLUSION BY RESEARCH TEAMS IN UGANDA - Uganda National Council for Science and Technology (UNCST, 2025)
This synthesis report examines the integration of gender equity and inclusivity within six International Development Research Centre (IDRC)-funded research projects implemented in Uganda under the Science Granting Councils Initiative (SGCI). The study assessed how gender considerations were incorporated into project design, implementation, leadership, participation, monitoring, and outcomes across projects in wheat production, cricket farming, essential oils, shea butter, maize bran bakery, and propolis commercialization. Using questionnaires, document reviews, stakeholder discussions, key informant interviews, and site visits, the study found varying levels of gender awareness but significant gaps in systematic gender mainstreaming. Most projects lacked gender-specific targets, dedicated budgets, comprehensive gender analyses, monitoring frameworks, and gender-disaggregated data collection. Nevertheless, several projects demonstrated positive outcomes, particularly in women's economic empowerment, income generation, skills development, and youth engagement. The report highlights the importance of integrating gender considerations from project inception, undertaking gender analyses, establishing gender-responsive monitoring systems, allocating dedicated resources, and strengthening institutional support mechanisms. Recommendations are provided for project teams and the Uganda National Council for Science and Technology (UNCST) to enhance gender-responsive research and innovation programming and contribute to more equitable and inclusive socioeconomic development in Uganda.
Preconditions and Success Factors A SYNTHESIS CASE STUDY REPORT
Keywords: Gender Equity; Gender Mainstreaming; Inclusivity; Research Projects; Science; Technology and Innovation (STI); Women's Empowerment; Gender Integration; Gender-Responsive Research; Science Granting Councils Initiative (SGCI); International Development Research Centre (IDRC); Socioeconomic Development; Gender Equality; Capacity Building; Monitoring and Evaluation (M&E); Uganda